PENGEMBANGAN MASYARAKAT PERDESAAN MELALUI PRAKTIK PEKERJAAN SOSIAL BERBASIS KOMUNITAS (Studi Kasus pada Kelompok Tani Wonosari II Kabupaten Kubu Raya Provinsi Kalimantan Barat): Studi Kasus pada Kelompok Tani Wonosari II Kabupaten Kubu Raya Provinsi Kalimantan Barat - Kurniawan Bagus Dwi Prayogo; Helly Ocktilia (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Agriculture is one of the main sources of income for rural communities. The lack of ability to be able to access information causes limitations in the development of agricultural systems and has an impact on the low level of the economy of the farming community. This study aims to describe the development of rural communities through the practice of community-based social work as an effort to address the problems of farmer groups. The study was conducted on a farmer group in a rural area in Kubu Raya Regency West Kalimantan Province. The research method used is a qualitative approach and case studies. The data collection process used interview, FGD, observation, and documentation studies. Social work interventions are implemented using the following strategies and tactics: (1) Collaboration strategies with implementation tactics and capacity building with techniques for expanding participation and empowerment; (2) Campaign strategy with education and training tactics. The results of the study show that efforts to handle problems in the farming community are carried out in a participatory manner using the stages in macro social work, from social initiation to termination and referral. The handling of problems is stated in the